Talking about pretend emotions: the relation between the syntax of complementation and the understanding of emotional simulation - Sidera-Caballero, Francesc; Amadó-Codony, Anna; Serrat-Sellabona, Elisabet (Anales de Psicología / Annals of Psychology, 2012)
This work aims at investigating the relationship between the use of the syntax of complementation and children’s ability to understand emotional simulation. A total of 337 children from four to twelve years of age were administered four tasks in which the characters simulated an emotion, whether to play or to deceive an observer. Participants were asked both about the external and the internal emotion of the protagonist, and also about the beliefs of the observer. Children were requested to justify their responses. Children’s ability to understand simulated emotions and their use of different types of sentential complement sentences were analysed. The results uncovered a significant contingency between children’s understanding of simulated emotions and their use of sentential complement sentences with cognitive or communicative verbs. However, the use of this type of sentences was not found necessary or sufficient for children to understand emotional simulation. The extent of the relationship between the understanding of emotional simulation and the use of sentential complement sentences is discussed.